Primary total hip arthroplasty versus hemiarthroplasty for displaced intracapsular hip fractures in older patients: systematic review. (11th June 2010) - Hopley, Colin; Stengel, Dirk; Ekkernkamp, Axel; Wich, Michael
Abstract : Objective To determine whether total hip arthroplasty is associated with lower reoperation rates, mortality, and complications, and better function and quality of life than hemiarthroplasty for displaced fractures of the femoral neck in older patients. Design Systematic review and meta-analysis of randomised trials, quasirandomised trials, and cohort studies. Data sources Medline, Embase, Cochrane register of controlled trials, publishers' databases, and manual search of bibliographies. Study selection Randomised controlled trials, quasirandomised trials, and cohort studies (retrospective and prospective) comparing hemiarthroplasty with total hip arthroplasty for treating displaced femoral neck fractures in patients aged more than 60 years. Data extraction Relative risks, risk differences, and mean differences from each trial, aggregated using random effects models. Analyses were stratified for experimental and non-experimental designs, and two way sensitivity analyses and tests for interaction were done to assess the influence of various criteria of methodological quality on pooled estimates. Data synthesis 3821 references were identified. Of the 202 full papers inspected, 15 were included (four randomised controlled trials, three quasirandomised trials, and eight retrospective cohort studies, totalling 1890 patients). Meta-analysis of 14 studies showed a lower risk of reoperation after total hip arthroplasty compared with hemiarthroplasty (relative risk 0.57, 95% confidence interval 0.34 to 0.96, risk difference 4.4%, 95% confidence interval 0.2% to 8.5%), although this effect was mainly driven by investigations without concealed treatment allocation. Total hip arthroplasty consistently showed better ratings in the Harris hip score (three studies, 246 patients, weighted mean difference 5.4, 95% confidence interval 2.7 to 8.2) after follow-up periods of 12 to 48 months. The standardised mean difference of different scores from five studies was 0.42 (95% confidence interval 0.24 to 0.61), indicating a medium functional advantage of total hip arthroplasty over hemiarthroplasty. Total hip arthroplasty was associated with a slightly higher risk of dislocation (relative risk 1.48, 95% confidence interval 0.89 to 2.46) and general complications (1.14, 0.87 to 1.48). Conclusion Single stage total hip arthroplasty may lead to lower reoperation rates and better functional outcomes compared with hemiarthroplasty in older patients with displaced femoral neck fractures. However, heterogeneity across the available trials and distinct subgroup effects preclude definitive statements and require further research in this area.